PERSPECTIVE OF ISLAMIC LAW ON HATE COMMENTS IN SOCIAL MEDIA - M.S Almujaddedi; Revi Hayati (STIH Putri Maharaja, 2022)
This study aims to analyze the perspective of Islamic law on hate comments that are rampant on social media so far. malicious comments (hate comments) in the comments column of social media that open up space for netizens to provide malicious comments (hate comments) to accounts contained in these social media sites. The use of insulting words, harassment, provocation, and unethical words will result in the destruction of the relationship of harmony and unity. This research is a library research using a qualitative approach. Research data is obtained by documenting journals, books, and articles related to the research topic. The results of this study are in the perspective of Islamic law, all forms of hate comments are haraam and believers should not do hate comments on social media so they don't get the rest.